Beyond the Theoretical Impasse: Extending the applications of Transactional Distance Education Theory - Sushita Gokool-Ramdoo (Athabasca University Press, 2008)
The development of theory in distance education is seen as crucial for its sustainability. Since the 1960s, there have been attempts to theorise distance education activities, to explain underlying initiatives and endeavours. Attempts at theorisation were started in the 1950s (Black, 2007). Wedemeyer (1961, cited in Garrison, 2000) introduced the concept of independent study or learning as opposed to correspondence education. Ever since, theory has been in ebullition, with various emerging tendencies. It has long been argued (for example Moore, 1993; Amundsen, 1993; Moore and Kearsley, 1996; Garrison, 2000; Saba, 2003) that there needs to be a global, comprehensive theory that can explicate all activities pertaining to distance education. While Moore has long claimed that the Transactional Distance Theory (TDT) is one such theory (Moore and Kearsley, 1996), there appears to be hesitance over accepting it as such, despite the fact that a transactional approach seems to be consciously or unconsciously adopted by theorists and practitioners alike. This apparent reluctance to hail the Transactional Distance Theory as a global theory has plunged distance education into a theoretical impasse from whence there was no much development. The emergence of two theoretical synergies has been noted (Saba, 2003, p.4) as has the need to develop a third and more comprehensive synergy. This research paper adopts the view that the theoretical impasse can be crossed with the recognition of Moore’s Transactional Distance Theory as the global theory that can explicate and ensure the sustainability of distance education in a technology-driven world. It further analyses its possible applications beyond simply the educational experience to encompass more general concerns like quality assurance and policy development. It is thus proposed that the Transactional Distance Theory be accepted as a global theory.